Exploring Gender on EFL Learners’ Beliefs about Language Learning - Sundari, Hanna; Hadi, Irfan; Nurhayati, Nurhayati (Lingua Cultura, 2014)
Article aimed to describe language learners’ belief system and to investigate how significance the language learners’ beliefs are between them in language learning. Using both qualitative and quantitative approaches, this research took 111 female- and 32 male-first semester college-students majoring in English Education as respondents. The instrument was 34-item BALLI questionnaire designed by Horwitz. The findings of the research showed that females and males’ language beliefs about language learning are mostly in similar fashion. The significant differences in responses were on the beliefs related to language and intelligence, enjoyment in practicing English, learning English-speaking cultures, having English-speaking friends, and motivation in learning English.